2017
DOI: 10.1097/poc.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Point-of-Care Diagnostics on Maternal Outcomes in Human Immunodeficiency Virus–Infected Women

Abstract: Introduction The World Health Organization advocates for increased accessibility of HIV-related point-of-care (POC) diagnostics in settings that lack laboratory infrastructure. The aim of this study is to assess the impact of POC diagnostics on maternal health outcomes in HIV-infected women. Methods A systematic literature review used multiple data sources as follows: Cochrane Infectious Disease Group Specialized Register; Cochrane Central Register of Control Trials, published in The Cochrane Library; PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Since the introduction of this strategy, the role of HIV rapid tests in diagnosing and facilitating linkage to treatment in various settings cannot be undermined. HIV rapid tests has been associated with decreased mother-to-child transmission of HIV, increased linkage to antiretroviral treatment and care for HIV-infected women [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of this strategy, the role of HIV rapid tests in diagnosing and facilitating linkage to treatment in various settings cannot be undermined. HIV rapid tests has been associated with decreased mother-to-child transmission of HIV, increased linkage to antiretroviral treatment and care for HIV-infected women [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that has evaluated the impact of syphilis POC testing on MMR in a high HIV prevalence resource-limited setting. Our recent systematic review has shown a lack of evidence on the impact of syphilis POC diagnostics on maternal outcomes of HIV-infected patients [4]. A quasi-experimental interrupted time series design was employed to determine the impact of syphilis POC testing on maternal mortality ratio (MMR) in KZN.…”
Section: Discussionmentioning
confidence: 99%
“…The report also shows that over a fifth of South African women in their reproductive ages (15-49 years) are HIV positive [3]. A recent report on maternal health indicates that non-pregnancy-related infections due to HIV/AIDS contribute to 43.7% of the total maternal mortality in South Africa [4]. The 2014 Amnesty International report on maternal health in KwaZulu-Natal (KZN) and Mpumalanga 2008-2010 highlights the barriers, such as poor access to health care, resulting in women and girls delaying or avoiding antenatal care in and maternal deaths [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, POC testing in emergency departments may result in timely discharge of patients, expediting triage of patients, and early treatment initiation, as well as alleviate the negative impacts of overcrowding [ 12 ]. Studies have demonstrated that POC testing has the potential to reduce the time to obtain test results and accelerate the diagnosis and initiation of treatment, particularly where healthcare infrastructure is weak and access to quality and timely medical care is a challenge [ 2 , 6 , 13 , 14 ]. Other studies have also proven that rapid POC testing delivers prompt results as well as early referrals when compared to standard laboratory testing [ 4 , 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%